Forensic mental health assessment in criminal contexts: key concepts and cases - Kaufman, Noah K. (Routledge, Taylor & Francis Group, 2022)
"This valuable compendium advances the understanding of mental health case law, making it highly accessible to practicing forensic professionals. Divided into two parts, the first section focuses on explaining important topics related to forensic psychological and forensic neuropsychological assessment, whilst the second section stands on its own as a collection of fascinating legal cases with high relevance to mental health and legal professionals interested in how mental health disorders impact criminal behavior among juveniles and adults. The book begins with an accessible primer on abnormal behavior, exploring the links between criminal behavior and mental health disorders. It goes on to thoroughly describe what goes into forensic psychological and forensic neuropsychological evaluations, including discussion about the Federal Rules of Evidence, as they pertain to evidence-generation during the mental health evaluation process. The book also focuses on psychometric concepts, including reliability, validity, sensitivity and specificity, as well as an exploration of 'science' and 'the law' which includes a discussion about the difference between science and pseudoscience, the different sources of law (constitutions, statutes, and case law), and how the intellectually competitive practice of law is similar to the enterprise of science. Ethical issues faced by the forensic mental health worker are also addressed. The second section of the book, Legal Cases for the Forensic Mental Health Professional, is an alphabetical summary of important and interesting legal cases with relevance for mental health professionals. These cases offer real-world significance whilst summarising complex legal decisions through a neuropsychological sieve, to allow both legal and psychological communities to better understand each other's professions. This book will be an invaluable resource for forensic psychologists, forensic neuropsychologists, forensic psychiatrists, and other mental health professionals whose work brings them into contact with the juvenile justice and adult criminal justice system. It will also be of interest to legal professionals, criminal justice departments and law schools"--